2012
DOI: 10.1037/a0027626
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of activation of thematic and functional knowledge during conceptual processing of manipulable artifacts.

Abstract: The current research aimed at specifying the activation time course of different types of semantic information during object conceptual processing and the effect of context on this time course. We distinguished between thematic and functional knowledge and the specificity of functional similarity. Two experiments were conducted with healthy older adults using eye tracking in a word-to-picture matching task. The time course of gaze fixations was used to assess activation of distractor objects during the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 64 publications
9
94
0
Order By: Relevance
“…Similarly, De Zubicary et al (2013) demonstrated left posterior middle temporal and inferior parietal activation in a functional imaging study in which target pictures to be named were paired with thematically-related distractor words to be ignored. In response to such data, we have proposed that thematic artifact relationship processing may frequently entail implicit activation of sensorimotor representations for using the objects together (Kalénine et al, 2012). The present evidence is compatible with these prior results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, De Zubicary et al (2013) demonstrated left posterior middle temporal and inferior parietal activation in a functional imaging study in which target pictures to be named were paired with thematically-related distractor words to be ignored. In response to such data, we have proposed that thematic artifact relationship processing may frequently entail implicit activation of sensorimotor representations for using the objects together (Kalénine et al, 2012). The present evidence is compatible with these prior results.…”
Section: Discussionsupporting
confidence: 82%
“…Some exceptions to this lack of evidence come from a recent eye-tracking study from our laboratory showing that thematic relationships are processed temporally earlier than relationships based on functional similarity (Kalénine et al, 2012). Thus, for example, when asked to locate target objects such as "broom" in an array, participants look more quickly at thematically-related distractors such as "dustpan" than functionally similar distractors such as "sponge," even though other types of (non-action) semantic relatedness were equivalent for these two distractor types.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, faster object processing may be observed when the features highlighted by response preparation are compatible with one of the actions evoked by the object. At the same time, visual object processing appears to activate action representations, even in tasks not involving a motor response (e.g., Kalénine, Mirman, Middleton, & Buxbaum, 2012; Lee et al, 2013; Myung et al, 2010). Additionally, visual context influences object processing (e.g., Gronau, Neta, & Bar, 2008; Mudrik, Lamy, & Deouell, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using the visual world paradigm have also found that function information becomes active after other, arguably more perceptually grounded, aspects of conceptual knowledge. For instance, knowledge about the thematic relationships that an object can participate in (i. e., the knowledge that a broom is often paired with/seen with a dustpan, or that a steak is paired/seen with a knife), and knowledge about an object's structural characteristics (its shape, size and volume) appear to become available more rapidly and more transiently than information about its function (see Kalénine, Mirman, Middleton & Buxbaum 2012 for thematic relationships and Lee, Middleton, Mirman, Kalénine & Buxbaum 2013 for structural relationships).…”
Section: Introductionmentioning
confidence: 99%